Website Design for Spiritual Items at The Catholic Church of Saint Lukas Parish Samarinda Using The Waterfall Method - Palayukan, Teresa Dominika; Pahrudin, Pajar; Rasyad, Rizky Zakariyya (ProBisnis : Jurnal Manajemen, 2025)
The purpose of this study is to design and build a website that provides information about spiritual objects in the Saint Luke Parish Catholic Church in Samarinda, with the hope of making it easier for the congregation to access the information. The method used in developing this website is the Waterfall method. This process includes the stages of needs analysis, system design, implementation, testing, and maintenance. Each stage is carried out sequentially to ensure that all aspects of the website can function properly. The results of this study indicate that the website that was built can provide accurate and easily accessible information about spiritual objects. In addition, this website is also equipped with features that make it easy for users to search for and obtain the information they need. The original value of this study lies in the development of a website that is specific to the needs of the Saint Luke Parish Catholic Church in Samarinda, which does not yet have an adequate digital platform to convey information about spiritual objects. This website is expected to be a useful source of information for the congregation and increase their involvement in church activities.